Carotenoid composition of Brazilian fruits and vegetables - Rodriguez-Amaya, D. B.; Amaya-Farfan, J.; Kimura, M. [UNESP]; Desjardins, Y. (Int Soc Horticultural Science, 2007)
Brazil has a wide diversity of food sources of carotenoids. The updated Brazilian database consists of more than 270 items of fruits, vegetables and their prepared and processed products. The database demonstrates variations due to variety, maturity, production technique, climate and processing. Many of these foods are not found in the US and European databases. Good to rich sources (>20 mu g/g) of beta-carotene are: acerola, bocaiuva, mango 'Extreme' and tucum (a) over tilde. Sources of both alpha-carotene and beta-carotene are buriti, carrot, Cucurbita moschata 'Menina Brasileira', 'Baianinha' and 'Goianinha', and red palm oil. Commercially produced and uncultivated or semi-cultivated leafy vegetables, C. maxima 'Jerimum Caboclo' and the hybrid Tetsukabuto, cooked broccoli are sources of lutein and beta-carotene. The edible Tropaeolum majus flower is especially rich in lutein. Although many fruits have beta-cryptoxanthin as principal carotenoid (e.g. caja, nectarine, peach, orange-fleshed papaya, tree tomato), the levels are below 20 mu g/g. Good to rich sources of lycopene are guava and guava products, papaya, pitanga and pitanga juice, tomato and tomato products, and watermelon. Sources of zeaxanthin are rare; although the principal carotenoid of piqui, the amount is low, lower than that found in buriti.
Keywords: beta-carotene; alpha-carotene; beta-cryptoxanthin; lycopene; lutein; zeaxanthin; food sources